Enhancement of Program Outcomes for Cryptography and Network Security Course Using Alternate Assessment Tool : An Approach towards Outcome-Based Education - M, Namratha; S, Selva Kumar; Sainath, Krishnamurthy (Journal of Engineering Education Transformations, 2023)
Outcome-based education is being practiced across the globe to enhance the employability of the undergraduates by instilling certain domain-specific skills. Evaluation is key in measuring the leaning outcomes of students. Tools such as regular quizzes, assignments, and alternative assessment are in place for continuous evaluation. Alternative assessment tools (AAT) can be modulated to suit the course being taught, and if used properly, it can enhance the attainment of program outcomes (PO). To enhance the coding skills of the students with respect to security algorithms and their real-time applications, for the course â€œCryptography and Network Securityâ€, in the computer science and engineering branch, AAT was introduced in the assessment process. Students were given a task to develop an algorithm using CryptTool and demonstrate the various attacks on the selected encryption/decryption algorithm. By using AAT, engagement of students was improved due to fortnightly reviews from the teacher, peer reviews, and exchange of ideas to go in the right direction in the work plan. The results show improvement in the attainment of program outcomes PO4 and PO5, which were not mapped when AAT was not yet implemented. In addition, the use of CrypTool as part of AAT helped the students in selecting suitable security projects in their higher semester courses.